Steep Trails - Muir, John (Gibbs Smith, 2021)
A patron saint of twentieth-century environmental activity, John Muir's appeal to modern readers is that he not only explored the American West but also fought for its preservation. Steep Trails collects together his essays and letters written as he traveled, capturing the personal, heartfelt connection he had with the lands he roamed.